Experimental description of heat transfer processes at two-phase flow in microchannels towards the development of a heat sink for PV panels - Pontes, Pedro; Marseglia, Guido; Perez, Mariana; de Giorgi, M. G.; Moreira, A. L. N.; Moita, Ana S. (Frontiers in Thermal Engineering, 2024)
The development of new and more effective cooling technologies is required for several high thermal power dissipation applications such as in electronics cooling or high concentrated photovoltaic panels. The present paper addresses an experimental study on the development of a microchannel based heat sink to cool photovoltaic panels. Experiments focus on the test of a microchannel, with geometry and dimensions optimized from previous work. The analysis performed here emphasizes the experimental characterization of flow boiling in the microchannel under different working conditions. The results include pressure drop and heat flux maps, obtained combining pressure sensors with high-speed imaging and time resolved thermography. The analysis performed was able to identify where nucleation sites were formed. Slug flow interfacial heat transfer could be observed and accurately described in the heat flux maps. Overall, results show the high potential of combining high-speed imaging with time resolved infrared thermography to characterize complex flows. These results also show that there is a good potential for this microchannel based flow cooling in removing the required heat fluxes for the application considered here, when compared to other liquid and air-cooling technologies.